2003
DOI: 10.1038/sj.bmt.1703809
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between two strategies for umbilical cord blood collection

Abstract: Summary:The use of cord blood (CB) for transplantation has increased greatly in recent years. The collection strategy is the first step in collecting good-quality CB units. There are two main techniques for collecting CB from the umbilical vein: in the delivery room while the placenta is still in the uterus by midwives and obstetricians or in an adjacent room after placental delivery by CB bank trained personnel. In this study, the benefits and disadvantages between the two different CB collection strategies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
2
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 17 publications
4
43
2
3
Order By: Relevance
“…At present, there is no international consensus on the procedure of UCB collection in maternity wards [21]. Results from a recent study demonstrated that the median concentrations of nucleated cells and total colony-forming units were significantly lower in UCB collected after placental delivery when compared to their counterparts collected before placental delivery [22]. Our results are in agreement with those presented by Surbek et al [23] and show also higher numbers of total nucleated cells and colony-forming units for in utero cord blood collections.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is no international consensus on the procedure of UCB collection in maternity wards [21]. Results from a recent study demonstrated that the median concentrations of nucleated cells and total colony-forming units were significantly lower in UCB collected after placental delivery when compared to their counterparts collected before placental delivery [22]. Our results are in agreement with those presented by Surbek et al [23] and show also higher numbers of total nucleated cells and colony-forming units for in utero cord blood collections.…”
Section: Discussionmentioning
confidence: 99%
“…In general cord blood, samples are between 60 and 120 ml, yielding 300 to 600 million mononuclear cells. Cord blood yields more mononuclear cells than adult blood (31,32), so to obtain a comparable number of PBMCs, we collected 150-200 ml of adult blood. This study was approved by the University of Arizona Human Subjects Committee, and written informed consent was obtained from all donors.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4] A number of CB banks collect and store placental blood from healthy infants after uncomplicated pregnancy and delivery. 5,6 Data from CB banks have offered an acceptable alternative for studying blood cell physiology, such as CD34 þ cells, [7][8][9] because it can be demanding to ethically justify blood sampling from healthy newborn infants.…”
Section: Introductionmentioning
confidence: 99%